Controversial mechanisms of methanol steam reforming: A review - Hassan, Amir (International Journal of Hydrogen Energy, 2024)
The relationship between the environment and energy is primarily due to the excessive use of fossil fuels. Natural resource depletion and climate change have led the scientific community to look for sustainable and cost-effective energy-saving technologies. Hydrogen has emerged as a promising fuel for various applications, and the methods explored for hydrogen production, is methanol steam reforming (MSR) which stands out due to its advantage such as high hydrogen yield, low-temperature activation. Despite its potential, challenges in hydrogen storage and transportation persist, prompting extensive research on effective catalysts for MSR. This review article focused on the controversial mechanisms of MSR, presenting a comprehensive exploration of different pathways, including methanol decomposition, methyl formate hydrolysis, methanol dehydrogenation, and formaldehyde/formic acid intermediates. The review article concludes various catalysts and their impact on MSR mechanism, highlighting the importance of catalyst activity and selectivity in mechanism, with a discussion on the Frank catalytic cycle of MSR, summarizing proposed pathways and intermediates. Overall, this review provides valuable insights into the complex and evolving field of methanol steam reforming, contributing to the understanding of reaction mechanisms and catalyst design for enhanced efficiency.
CRIS-Team Scopus Importer:2024-11-15
Keywords: And frank catalytic cycle; Formaldehyde and formic acid intermediates; Hydrogen; Mechanisms; Methanol decomposition; Methanol steam reforming; Methyl formate hydrolysis